The mapping competences of the nurse Case/Care Manager in the context of Intensive Care - Alfieri, Emanuela; Ferrini, Anna Chiara; Gianfrancesco, Francesca; Lise, Gianluca; Messana, Giovanni; Tirelli, Lorenzo; Lorenzo, Ana; Sarli, Leopoldo (Acta Biomedica Atenei Parmensis, 2017)
Background and aims: Since the recent introduction of the Case/Care Manager’s professional figure, it is quite difficult to identify properly his/her own particular features, which could be mainly be found revising mainly in American studies. Therefore, the present study intended to identify the Case/Care Manager’s skills and professional profile in an Intensive Care Unit experience, taking into consideration the staff’s activities, perception and expectations towards the Case/Care Manager. In particular, it has been compared the experience of an Intensive Care Units where the Case/Care Manager’s profile is operational to a different Unit where a Case/Care Manager is not yet in force. Method: a Levati’s model was used to map the Case/Care Manager’s skills, involving each unit whole working staff, executives and caregivers through semi-structured interviews. It has been taken into consideration the Anaesthesia Unit and Emergency Unit of Cesena’s healthcare organisation (AUSL of Romagna) and a Cardiology Intensive Care Unit of Piacenza’s healthcare organisation, where the Case/Care Manager’s profile has not been experimented yet. Firstly, it a data collection in each healthcare organization has been organised. Subsequently, semi-structured interviews to doctors, unit nurses, caregivers, nurses’ coordinators and medical staff have been used to compare each healthcare system. The interviewees’ described their expectations in relation to the Case/Care Manager working in a critical area. Then, every data collected during interviews has been organised to map a Case/Care Manager’s essential professional profile to work in a critical area together with medical staff. Results: Piacenza’s O.U. critical area experience reported a major demand for patients’ and patient’s families’ assistance. On the other hand, the very same aspects seem to have been better achieved in Cesena’s O.U., where a Case/Care Manager’s recent introduction has actually helped to overcome the void in organising systems. Conclusions: a Case/Care Manager’s profile has been drafted on the basis of the comparative analysis conducted. It has been noted how the Case/Care Manager’s professional profile can really improve relationships and communications between medical staff and patients, promoting a major unity among the working team. According to the present research, the Case/Care Manager’s profile has been proved helpful in positively influencing the team activity and to elicit major satisfaction both in patients and their family.